Ahmad Dahlan’s Perspective on the Model of Modern Integration of Islamic Education - Ahwan Fanani (Nadwa: Jurnal Pendidikan Islam, 2019)
Ahmad Dahlan made a breakthrough in Islamic Education in the Early 20th Century. He was not only educated in a traditional environment, but also influenced by the modernist movement in Egypt, especially Abduh and Rashid Ridla. This article aims to describe the approach of modern Islamic education by Ahmad Dahlan. This writing uses the socio-historical approach. The results show that Dahlan renewed Islamic Education by integrating Islamic subjects into the public school curriculum and vice versa. The project covers aspects of curriculum, methods, and institutions. Integration projects are more practical and in line with projects undertaken by Ismail Raj'i al-Faruqi, Naquib al-Attas, and Amin Abdullah. The modern Islamic education model by Ahmad Dahlan is relevant to current Islamic education. AbstrakAhmad Dahlan melakukan terobosan dalam Pendidikan Islam di Awal abad 20. Beliau tidak hanya dididik di lingkungan tradisional, tetapi juga dipengaruhi oleh gerakan modernis di Mesir, terutama Abduh dan Rashid Ridla. Artikel ini bertujuan untuk menggambarkan pendekatan pendidikan Islam modern oleh Ahmad Dahlan. Penulisan ini menggunakan pendekatan sosial-sejarah. Hasilnya menunjukkan bahwa Dahlan memperbarui Pendidikan Islam dengan mengintegrasikan mata pelajaran Islam ke dalam kurikulum sekolah umum dan sebaliknya. Proyeknya mencakup aspek kurikulum, metode, dan kelembagaan. Proyek integrasi lebih bersifat praktek dan sejalan dengan proyek yang dilakukan oleh Ismail Raj'i al-Faruqi, Naquib al-Attas, dan Amin Abdullah. Model pendidikan Islam modern oleh Ahmad Dahlan relevan dengan Pendidikan Islam saat ini.